Advancing Development with Mobile Phone Locational Data : Improving the Effectiveness of Assistance - Haddad, Ryan; Kelly, Timothy; Leinonen, Teemu; Saarinen, Vesa (World Bank Group, Washington, DC, 2015)
Mobile phones, and especially smartphones, are opening new ways to assess and improve assistance and the delivery of basic services in the developing world. Each year, developing countries see an annual gain of about 500 million new smartphones, virtually all of which generate not only call data records but also, with their GPS and Wi-Fi capabilities, a rich set of more precise data on location and movement. The rapid diffusion of the phones and the locational data they generate are helping fuel the science of delivery, the evidence-based, experimental approach to project assessment and improvement. The technology is finding an expanding variety of uses. Recent examples involving transport and logistics include: transit route mapping in Abidjan; supply chain management for community health workers in Malawi; transport planning in Cote d’Ivoire; and malaria tracking in Kenya. A notable and more impromptu use arose after a tsunami hit Japan in March 2011. Health care authorities used call data records (CDRs) generated by mobile phones to track the evacuation from the vicinity of the damaged Fukushima nuclear power plant. They then meshed the CDRs with health records to optimize the delivery of needed emergency health treatment.